2019
DOI: 10.1093/europace/euz246
|View full text |Cite
|
Sign up to set email alerts
|

European Heart Rhythm Association (EHRA) international consensus document on how to prevent, diagnose, and treat cardiac implantable electronic device infections—endorsed by the Heart Rhythm Society (HRS), the Asia Pacific Heart Rhythm Society (APHRS), the Latin American Heart Rhythm Society (LAHRS), International Society for Cardiovascular Infectious Diseases (ISCVID) and the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) in collaboration with the European Association for Cardi

Abstract: Pacemakers, implantable cardiac defibrillators, and cardiac resynchronization therapy devices are potentially life-saving treatments for a number of cardiac conditions, but are not without risk. Most concerning is the risk of a cardiac implantable electronic device (CIED) infection, which is associated with significant morbidity, increased hospitalizations, reduced survival, and increased healthcare costs. Recommended preventive strategies such as administration of intravenous antibiotics before implantation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
354
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(373 citation statements)
references
References 201 publications
3
354
1
15
Order By: Relevance
“…Various factors described in studies have been reported to predispose to PPM/ICD. These vary from either being patient centered or linked to procedural techniques or device related 15 . A meta-analysis from pooled anaysis comprising of 206,176 patients showed that Esrd, Copd, diabetes, fever were commonly seen among patients who developed infection while duration, pocket hematoma, inexperienced operator, temoprary pacing wire, abdominal location, epicardial leads were some of the procedure and device related risk factors 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors described in studies have been reported to predispose to PPM/ICD. These vary from either being patient centered or linked to procedural techniques or device related 15 . A meta-analysis from pooled anaysis comprising of 206,176 patients showed that Esrd, Copd, diabetes, fever were commonly seen among patients who developed infection while duration, pocket hematoma, inexperienced operator, temoprary pacing wire, abdominal location, epicardial leads were some of the procedure and device related risk factors 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood cultures were sent in 12 (85.7%) of cases and swab from pocket for culture and sensitivity was sent in all. All but 2 (85.7%) cases samples were drawn before any antibiotic was given although guidelines recommend obtaining cultures prior to the institution of antibiotic therapy 15 . No growth was seen in any of the pocket swabs but microbes were identified in 3 (21.4%) of the cases from blood samples.…”
Section: S874mentioning
confidence: 99%
“…At the time of the skin incision and device implantation, the patient’s own skin flora could be introduced in the wound and subsequently lead to pocket infection. This direct contamination via pocket erosion is a reason why stabilizing and fixating the pocket could contribute to primary prevention of CIED infections [ 5 , 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…It emphasizes the need for continuous monitoring of implant patients by maintaining a registry both at the national and international levels. Also, this document recommends research evidence for the use of antibiotic coated implants in minimizing infections and implant failures, duration of postoperative antibiotic therapy, appropriate timing for reimplantation surgeries, and the long term risk of death due to implant infection-related and other complications [ 38 ].…”
Section: Reviewmentioning
confidence: 99%